Maskless milling of diamond by a focused oxygen ion beam - Martin, Aiden A. (Sci Rep, 2015)
Recent advances in focused ion beam technology have enabled high-resolution, maskless nanofabrication using light ions. Studies with light ions to date have, however, focused on milling of materials where sub-surface ion beam damage does not inhibit device performance. Here we report on maskless milling of single crystal diamond using a focused beam of oxygen ions. Material quality is assessed by Raman and luminescence analysis, and reveals that the damage layer generated by oxygen ions can be removed by non-intrusive post-processing methods such as localised electron beam induced chemical etching.